Photosynthesis in Lichen: Light Reactions and Protective Mechanisms - Gasulla, Francisco; Herrero, Joaquín; Esteban-Carrasco, Alberto; Ros-Barceló, Alfonso; Barreno, Eva; Zapata, José Miguel; Guéra, Alfredo (IntechOpen, 2012)
None